Pengembangan Buku Panduan Berbasis Problem Solving dalam Meminimalisir Kekhawatiran pada Kelas Speaking Mahasiswa Program Studi Bahasa Inggris IKIP PGRI MADIUN - Fitra Pinandhita; Ratih Christiana (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2015)
Study aims to explain the application of guidebooks in minimizing concerns on speaking class students of English Teachers IKIP PGRI MADIUN. Methodology of writing using methods developed for the study, developed teaching materials. Based on observations at the Teachers IKIP PGRI MADIUN third semester students of English Education courses are approximately 70% of the students who this concern when performing exams speaking. Data collection techniques in this study are observation, interviews, documentation, and testing during learning process to determine the speaking abilities of students. Outcomes of this study is in the form of guide books, articles published in national online journals is not accredited and is also manifested in the scientific seminar national and international scale. According to the research, high criteria, quite, low before was low 4 student, quite 24 students, and one student in terms of high pretest. Researchers suggest that efforts should be made to help reduce the level of student concerns are still high is to optimize the service